Public Private Partnership Dalam Penyediaan Layanan Transportasi Publik Wira Wiri Suroboyo Di Kota Surabaya - Waradana, Farhan Kusuma; Priambodo, Bayu (Jurnal Administrasi Politik dan Sosial, 2024)
Public transportation in Surabaya faces various challenges, including severe congestion due to the dominance of private vehicles, inadequate facilities, insufficient routes, and issues with cleanliness, comfort, and safety. Collaboration between the government and the private sector through the Public Private Partnership (PPP) concept is considered a potential solution to build the necessary infrastructure, address government budget constraints, and improve the quality of public transportation. Further research on public transportation regulations in Surabaya is needed to enhance services and attract more users. This study focuses on the PPP model, which consists of 1. Project preparation, 2. Forms of cooperation, 3. Cooperative relationships. The research employs a descriptive method with a qualitative approach. The results of the study indicate that efforts to integrate transportation modes such as Suroboyo Bus and Wira Wiri Suroboyo show progress but are not yet sufficient to meet the needs of residents.